Intraoperative kinematic evaluation with navigation system and postoperative kinematic evaluation with dynamic RSA of total knee arthroplasty - Bruni, Danilo <1978> (Alma Mater Studiorum - Università di Bologna, 2014)
Restoring a correct implant kinematics and providing a good ligament balance and patellar tracking is mandatory to improve clinical and functional outcome after a Total Knee Replacement. Surgical navigation systems are a reliable and accurate tool to help the surgeon in achieving these goals. The aim of the present study was to use navigation system with an intra-operative surgical protocol to evaluate and determine an optimal implant kinematics during a Total Knee Replacement.